Rethinking professionalization: A generative dialogue on CSR practitioners1. Issue 2 (8th May 2019) - Brès, Luc; Mosonyi, Szilvia; Gond, Jean-Pascal; Muzio, Daniel; Mitra, Rahul; Werr, Andreas; Wickert, Christopher
Abstract: Studies of emerging professions are more and more at the crossroad of different fields of research, and field boundaries thus hamper the development of a full-fledged conversation. In an attempt to bridge these boundaries, this article offers a 'generative dialogue' about the redefinition of the professionalization project through the case of corporate social responsibility (CSR) practitioners. We bring together prominent scholars from two distinct academic communities—CSR and the professions—to shed light on some of the unsolved questions and dilemmas around contemporary professionalization through an example of an emerging profession. Key learnings from this dialogue point us toward the rethinking of processes of professionalization, in particular the role of expertise, the unifying force of common normative goals, and collaborative practises between networks of stakeholders. As such, we expand the research agenda for scholars of the professions and of CSR.